Profile of microbial community of naturally fermented Sumbawa mare’s milk using next-generation sequencing - Yoga Dwi Jatmiko; Irfan Mustafa; Tri Ardyati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2019)
This study aimed to investigate the bacterial and fungal/yeast diversity in naturally fermented Sumbawa mare’s milk through a next-generation sequencing approach, and evaluate the quality of fermented mare’s milk based on the presence of pathogenic or undesirable microorganisms. Microbial density determined using plate count agar (total aerobic bacteria), de Man Rogosa Sharpe agar (Lactobacillus), M17 agar (Lactococcus) and yeast peptone dextrose agar supplemented with streptomycin 50 ppm (yeast). Nutritional content and acidity level of each fermented milk sample were also evaluated. Genomic DNA was extracted using FastDNA Spin (MPBIO). The total gDNA was further analyzed using illumina high-throughput sequencing (paired-end reads), and the sequence results were analysed using QIIME v.1.9.1 to generate diversity profiles. The difference in nutrient content of mare’s milk was thought to affect the density and diversity of microbes that were able to grow. Fermented mare’s milk samples from Sumbawa had the highest bacterial diversity compared to samples from Bima and Dompu. However, fermented mare’s milk from Dompu had the best quality which was indicated by the absence of bacteria that have the potential to be pathogenic or food spoilage, such as members of the Enterobacteriaceae family (Enterobacter, Klebsiella and Escherichia-Shigella) and Pseudomonas. Genus of Kazachstania and Kluyveromyces, as well as family Dipodascaceae were frequently observed fungi/yeast from Sumbawa fermented mare’s milk. The presence of potential pathogenic bacteria warrants special attention in improving the hygiene of manufacturing process.